Prevalence of vitamin D deficiency in patients of pregnancy induced hypertension - Kaur, Guljit; Pahwa, Sangeeta; Preet, Ibadat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objectives of this study were to compare the serum Vitamin D levels in pregnant patients of pregnancy induced hypertension (PIH) and healthy normotensive patients and to study the prevalence of vitamin D deficiency in patients of PIH. Methods: This study was conducted in Shri Guru Ram Das Institute of Medical Sciences and Research, Vallah, Amritsar in year 2015-2017. In total 100 cases were taken for the study and divided into two groups. Results: Serum Vitamin D levels were quite low in women with pregnancy induced hypertension with a mean vitamin D levels of 13.006±6.24 ng/ml as compared to 23.239±10.601 ng/ml in healthy pregnant women. The prevalence of vitamin D deficiency in PIH group was very high i.e. 94% compared to 46% in normotensive group (Mean Vitamin D levels <20 ng/ml). Conclusions: Vitamin D levels are deficient in patients of PIH and there is increased prevalence of vitamin D deficiency with PIH suggesting that vitamin D deficiency can be a risk factor for the development of PIH.